PENINGKATAN HASIL BELAJAR MATA PELAJARAN MEMELIHARA TRANSMISI DENGAN MODEL PEMBELAJARAN LANGSUNG MELALUI PENERAPAN PENDIDIKAN KARAKTER PADA SMK NEGERI SURABAYA - Saputro, Prasetyo Dono (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2014)
This research aims to:1).Find the difference of student?s study result (affective, cognitive and psychomotor) who are taught by using direct instruction on the character education and those who are taught without character based education; 2). Find the difference of student?s learning motivation between those who are taught by using direct instruction on the character education and those who are taught without character based education.This sample of this research are student of 2nd grade TKR at SMK Negeri 3 Surabaya and SMK Negeri 5 Surabaya. There are 25 students. This research method used is Quasi Experimental Design by using Nonequivalent Control Group Design. This research is compared two classes. There are controlled and experimental class. The control class is the class which is taught by using direct instruction without character based education, while experimental class is the class which is taught by using direct instruction and character based education. The data of the student?s study result and learning motivation which are analyzed as follows: 1). Cognitive: Student?s cognitive study result is collected through the range between pretest score and post test score, 2). Psychomotor : Psychomotor study result is taken from the LP3 Score (Psychomotor), 3).Affective : Affective study result is taken from the average of LP4 Score(Affective), 4). Student learning motivation: Student learning motivation is taken from questionnaire related to student?s learning motivation. The research data is related to the hypothesis test by using T test (? = 0,05) are as follows: 1). Student?s study result at 2nd grade TKR of SMK Negeri 3 Surabaya are: a). Affective by using hypothesis test gets t count = 2.138 , t count > t table (2.138 > 1.679), therefore H1 is accepted; b). Cognitive by using hypothesis test gets t count = 1.517, t count ? t table (1.517 ? 1.679), therefore H1 is rejected; c). Psychomotor by using hypothesis test gets t count = 2.127 , t count > t table (2.127 > 1.679), therefore H1 is accepted; d). Learning motivation by using hypothesis test gets t count = 1.767, t count > t table (1.767 > 1.679), therefore H1 is accepted. 2). Student?s study result at 2nd grade TKR of SMK Negeri 5 Surabaya are as follows: a). Affective by using hypothesis test gets t count = 2.288, t count > t table (2.288 > 1.679), therefore H1 is accepted; b). Cognitive by using hypothesis test gets t count = 1.564, t count ? t table (1.564 ? 1.679), therefore H1 is rejected; c). Psychomotor by using hypothesis test gets t count = 2.252, t count > t table (2.252 > 1.679), therefore H1 is accepted; d). Learning motivation by using hypothesis test gets t count = 2.005, t count > t table (2.005 > 1.679), therefore H1 is accepted. Based on the data analysis above, it can be concluded that: 1). Student?s study result (affective,psychomotor) at the direct instruction by using character based education is better than without using character based education. However, student?s study result (cognitive) in the direct instruction by using character based education is not better than without using character based education. 2). Student?s learning motivation in the direct instruction by using character based education is better than without using character based education. Keywords: improving study result, direct instruction , character based education